Right Ventricular Functions in Patients Undergone Balloon Valvuloplasty for Isolated Pulmonary Valve Stenosis - Nagehan Katipoğlu; Mehmet Küçük; Timur Meşe; Rahmi Özdemir; Murat Muhtar Yılmazer; Utku Karaarslan (Galenos Publishing House, 2019)
INTRODUCTION: Pulmonary valve stenosis is the most common of the right ventricular outflow tract obstruction, BVP has been the treatment of choice in these subgroup of patients. In this study, we aimed to evaluate right ventricular functions of patients undergone BVP for PS using two-dimensional, pulse wave (PW) Doppler and tissue Doppler echocardiography. METHODS: 33 patients undergone BVP for PS (11 female, 22 male; mean age 7.7 +- 5.6 years) and age and gender-matched healthy 50 children were evaluated. RESULTS: In our study, the two-dimensional echocardiography derived TAPSE, RVED and RVFAC values; PW Doppler echocardiography derived tricuspid E and A waves, E/A ratio, and ET; tricuspid S and E wave, E/A ratio and ET obtained from tissue Doppler echocardiography were found to be lower in the patient group. IVRT and IVCT values obtained from both tissue Doppler and PW Doppler echocardiography, and the Tei index, were found to be increased in the patient group. Pulmonary insufficiency after BVP was present in 21.2% of the patient group DISCUSSION AND CONCLUSION: BVP appears to be a safe and effective option in treatment of congenital pulmonary valve stenosis. Presence of residual stenosis after BVP is found to be associated with right ventricular failure. Increased Tei index showed the presence of impaired right ventricular functions in patients undergone BVP for PS.